The reality of the organizational climate and its relationship to achievement motivation among sports coaches in sports units at some universities in the Kurdistan Region of Iraq - Rasul, Asst.L. Bakhtiyar Latif; Muhammad, Asst.L. Shayan Abdullah (Sulaimani Journal for Humanities, 2026)
This research aims to identify the organizational climate in the sports units of some universities in the Kurdistan Region of Iraq, to identify the achievement motivation of sports coaches in the sports units of some universities in the Kurdistan Region of Iraq, to identify the relationship between the organizational climate and the achievement motivation of sports coaches in the sports units of some universities in the Kurdistan Region of Iraq, and to identify the differences between male and female coaches in terms of organizational climate and achievement motivation in the sports units of some universities in the Kurdistan Region of Iraq. The researchers used a descriptive approach with correlational analysis to suit the nature of the research. The research population consisted of sports coaches in the sports units of universities in the Kurdistan Region of Iraq, specifically the universities of Sulaimani, Salahaddin, Duhok, Koya, Garmian, Halabja, Garmaw, and Soran, totaling 78 coaches. The research sample comprised coaches from the same universities, totaling 70 coaches, representing 89.74% of the population. The researchers utilized two scales: organizational climate and achievement motivation. The scientific basis for these scales was established after conducting a pilot study, followed by the main experiment. The researchers used the Statistical Package for the Social Sciences (SPSS) to process the data. The researchers concluded that the research sample exhibits an average level of organizational climate and achievement motivation within the sports units of some universities in the Kurdistan Region of Iraq, and that there is no correlation between these levels. The study examines the relationship between organizational climate and achievement motivation among sports unit coaches at some universities in the Kurdistan Region of Iraq. The researchers recommend focusing on the organizational climate within the sports units of the universities included in the study and working to increase achievement motivation among sports coaches at these universities.